Kaitan Kinerja Kepolisian Dengan Unsur Lokalitas Masyarakat (Studi Kasus Amuk Massa di Wilayah Polres Cilacap) Relation between Police Performance and Society Locality Element (A Case Study of Riot in Cilacap Resort Poli - Perpustakaan UGM, i-lib ([Yogyakarta] : Sekolah Pascasarjana Universitas Gadjah Mada, 2003)
ABSTRACTPolice and society are related component each other in realizing order and giving secure and order feeling in society. The position of police should be central in the society. In Cilacap Regency, during 1999, riots often occur that cause deaths and material damaging. In other side, the people there have a culture related to its area condition.The objectives of this study were, first, to know how much locality relate to performance of Cilacap Resort Police. Second, to identify society culture that could support police tasks in Cilacap in order to increase police performance. To understand deeper the vent, researcher raised problems "(1) To what extent Cilacap Resort Police consider locality element in resolving riot. (2) To what extent the output of performance of Cilacap Resort Police approach in resolving riot". In collection data and information as well as stuty analysis, researcher used a descriptive method.The result of the analysis indicated that the culture of Cilacap society still exist and is obeyed in life order of Cilacap society but not all are accommodated by Cilacap Resort Police in dealing with riot event. Each Sector police differently determines police in dealing with the riot. In law enforcement there is Head of Sector Police that implemented sociologic approach in dealing with riot with consideration that the approach can aliminate negative impact and accommodate society culture, whereas a juridical approach is still socialized intensively. Babinkamtibmas as the member of the police who should be among the society, has not done his job well. In riot event, police service and protection to ward the people is not experienced entirely because police is not responsive to the people is report, so the people have a less Reliance on police capability.